Livestock health and disease economics: a scoping review of selected literature - Kappes, Alexander; Tozooneyi, Takesure; Shakil, Golam; Railey, Ashley F.; McIntyre, K. Marie; Mayberry, Dianne E.; Rushton, Jonathan; Pendell, Dustin L.; Marsh, Thomas L. (Frontiers in Veterinary Science, 2023)
Animal diseases in production and subsistence environments have the potential to negatively affect consumers, producers, and economies as a whole. A growing global demand for animal sourced food requires safe and efficient production systems. Understanding the burden of animal disease and the distribution of burden throughout a value chain informs policy that promotes safe consumption and efficient markets, as well as providing more effective pathways for investment.This paper surveys existing knowledge on the burden of animal disease across economic categories of production, prevention and treatment, animal welfare, and trade and regulation. Our scoping review covers 192 papers across peer-reviewed journals and reports published by organizations.We find there exists a gap in knowledge in evaluating what the global burdens of animal diseases are and how these burdens are distributed in value chains. We also point to a need for creating an analytical framework based on established methods that guides future evaluation of animal disease burden, which will provide improved access to information on animal health impacts.